PENGEMBANGAN MEDIA PEMBELAJARAN MINIATUR BUDAYA INDONESIA BERBASIS PETA DIGITAL MATERI KEKAYAAN BUDAYA INDONESIA - Revina Alifia Amanda; Wawan Syahiril Anwar; Tatang Muhajang (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Revina Alifia Amanda. 037121122. Development of Indonesian CulturalMiniature Learning Media Based on Digital Maps of Indonesian Cultural WealthMaterials. The digital map-based learning media of Indonesian Miniature Culturefunctions as a tool for teachers in the teaching process, with the aim of deliveringmaterial to students through a combination of technology and the use of images andvideos. This research aims to create a learning media for Indonesian MiniatureCulture that focuses on Indonesian cultural richness materials, using the Researchand Development (R&D) method and the ADDIE model, which includes stages(Analysis, Design, Development, Implementation, and Evaluation). This researchwas conducted at SDN Ciheuleut 2 Bogor City in grade IV, involving one teacherand 24 students as respondents. The results of the study show that thedevelopment of this learning media meets the criteria is very feasible. The averagepercentage of assessments from media experts reached 96%, linguists 83%,material experts from lecturers 73%, material experts from teachers 92%, as well asthe results of the teacher response questionnaire 94% and student responses 97%.